(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to develop an efficient protocol for in vitro regeneration of mungbean (Vignaradiata) on the aspect of regeneration potentiality of two mungbean varieties (BINA mung 5 and BINA mung 7) as influenced by different combinations of growth regulators supplemented with MS medium. Cotyledon explant of both varieties was used for the present study. Data were collected for various characters of callus initiation, shoot regeneration and root proliferation. Initiation of callus (%) and required days for its initiation and weight of callus were influenced significantly due to the effect of varieties where BINA mung 5 produced more callus induction (40.36%) at minimum requiring time (18.27 days) including heavier sizes of callus (1.54 g) than BINA mung 7 when BINA mung 5 further recorded the longest root (2.92 cm) compare to BINA mung 7. Effect of treatments of the present study were significantly influenced the whole characters regarding callus culture, shoot regeneration and root proliferation. The highest percentage of callus (88.44%) within minimum time (12.53 days) including larger sizes callus (3.521 g) were produced in 1.0 mg L1 BAP + 2.5 mg L1 NAA among the treatments while the highest percentage of regenerated shoot (83.44%) at minimum requiring time (17.59 days) and more shoots (7.69 callus1) were obtained in 1.0 mg L1 BAP + 2.0 mg L 1 NAA. Root induction (82.50%), number of roots plantlet1 (8.469) with minimum requiring time for initiation (14.13 days) and root length (5.250 cm) were the highest in 0.2 mg L1 IAA + 1.0 mg L1 kinetin + 0.2 mg L1 BAP. Incase of interaction, percentage of callus initiation (89.38 %) was the highest in BINA mung 5 treated by 1.0 mg L1 BAP + 2.5 mg L1 NAA at requiring minimum time (12.38 days) while same treatment produced the larger callus (3.581 g) among the interactions. The highest percentage (84.38%) and number (7.813 callus1) of shoot with minimum requiring time (17.50 days) were found from BINA mung 5 treated by 1.0 mg L1 BAP + 2.0 mg L1 NAA. Similarly, the longest shoot (5.58 cm) was produced from the BINA mung 5 treated by 1.0 mg L1 BAP + 2.0 mg L1 NAA. However, root induction (%), roots plantlet1, days required for root initiation and root length were statistically similar among the whole interaction treatments due to non significant variation. This result mentioned that the variety BINA mung 5 was better than BINA mung 7 for callus induction, shoot regeneration and root initiation while 1.0 mg L1 BAP + 2.5 mg L1 NAA, 1.0 mg L1 BAP + 2.0 mg L1 NAA and 0.2 mg L1 IAA + 1.0 mg L1 kinetin + 0.2 mg L1 BAP supplemented with MS medium were the best combinations for better callusing, higher ability of shoot regeneration and root proliferation. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22203 J. Environ. Sci. & Natural Resources, 7(2): 47-52 2014